Exclusive Breastfeeding and Factors Influencing Its Abandonment During the 1st Month Postpartum Among Women From Semi-rural Communities in Southeast Mexico - Vázquez-Osorio, Inocente Manuel; Vega-Sánchez, Rodrigo; Maas-Mendoza, Eric; Heller Rouassant, Solange; Flores-Quijano, María Eugenia (Frontiers in Pediatrics, 2022)
Introduction: In this study we describe breastfeeding practices among women from semi-rural communities in southeast Mexico, and explore which factors, modifiable or not, are associated with such practices. Materials and methods: This was a formative cross-sectional study that included 143 mothers with infants 4-6 months old, from semi-rural communities in Tabasco, Mexico. We collected data on two categories of factors: 1) women’s sociodemographic characteristics, and 2) maternal / infant factors. We first analyzed the frequency of various breastfeeding practices. Then, we classified participants into the up to one month of exclusive breastfeeding group (≤1m-EBF) and the beyond one month EBF group (>1m-EBF), if they practiced EBF for less or more than one month, respectively. We compared the two categories of factors between groups and then, using logistic regression models, explored which factors were associated with practicing >1m-EBF. Results: By the end of the first month postpartum, 51.7% of participants had abandoned EBF, introduced milk formula (35%), other food (9.1%), non-nutritive liquids (7.7%), or had stopped breastfeeding completely. In the next months, EBF practice fell sharply and mixed feeding grew importantly. Logistic regression models showed that women were more likely to be in the >1m-EBF group if they lived with the baby’s father, had complications during pregnancy, delivered vaginally and attended a health center at least three times postpartum. To the contrary, women were less likely to be practice >1m-EBF if they gave infants other liquids during their hospital stay; experienced pain or discomfort in breasts/nipples, or used a pacifier after hospitalization; had larger bodies (i.e. higher BMI); and believed that you should give the infant powdered milk or some other food when the baby is not full. Conclusions: Many factors associated with abandoning EBF, particularly in the early postpartum period, are modifiable and can be altered through timely interventions that include giving correct information and ensuring its comprehension; assertive personal counseling and accompaniment must be provided to mothers; and reinforcement during the early postpartum at health facilities and other settings.